Pengaruh Online Distribution Channels (ODS) Terhadap Hotel Revenue - Suci Sandi Wachyuni; Kadek Wiweka; Melyana Liman (STIE Pariwisata API Yogyakarta, 2018)
The trend of market developments or consumers in utilizing technology as part of their lifestyle, encourages the accommodation industry to make innovations related to technology and the internet. The purpose of this study is to see the relationship between online distribution channels, especially OTAs on hotel performance in terms of income. This study found that OTA was very effective in increasing sales at Dreamtel Hotel Jakarta, where the income originating from OTA for 3 years compared to walk-in guests had a significant difference. However, hotel sales through online travel agents still have problems when using an online booking system, including the delays in connection between the online travel agent system and hotel systems, the difficulty of changing the schedule for booking rooms, and booking based on